Model identification adaptive control - implementation case studies for a high manoeuvrability aircraft - Öreg, Zsombor; Shin, Hyo-Sang; Tsourdos, Antonios (Institute of Electrical and Electronics Engineers (IEEE), 2019)
With the proliferation of modular Unmanned Aerial Vehicles (UAVs) cheap and scalable control methods are needed to ensure operability. Using adaptive control it seems that these requirements could be met. In this paper applicability of parameter adaptation and control methods are demonstrated within the model identification adaptive control framework, implementing several methods and evaluating their performance. As a plant a non-linear simulation model of an F-16 aircraft is used.
Keywords: Wireless fidelity; 3GPP; Channel allocation; Computer architecture; 5G mobile communication; Privacy